Fringe Field Assisted Electrostatic Discharge in Polypropylene Manufacturing - Charoensorn, Panudda; Srisonphan, Siwapon; Kanokbannakorn, Weerawoot; Kasemsuwan, Varakorn (My University, 2020)
Polypropylene (PP) is an electrical insulation material, and it can store electrostatic charge easily once they have friction with the metal or rubber rollers. Herein we present electrostatic issues in non-woven fabric manufacturing based on the roll to roll production processes. By using portable electrostatic-field meter measurements, we provide a low-cost and highly effective solution for discharging electrostatic charge before exposed or in contact with the operators, and we also identify where to install charge-dissipation technology to make it most useful. We employed the benefit of a highly and localized fringe field to discharge the electrostatic charge along the edge of the grounded metal rod placed at ~30 cm away. After placing the metal rod, the average of electrostatic potential of winding stock roll during spinning is decreased ~10 times, corresponding to ~0.2 μc/m3 accumulated electrostatic charge on synthetic fabrics. The electric field distribution via the finite element method was illustrated corresponding to the reduction of electrostatic charge distribution in PP winding stock roll before and after inserting the grounded metal rod.
Keywords: Electrostatic discharge; Electrostatic potential; Fringe field.; Insulation; Polypropylene